Production, Characterization, and Molecular Phylogenetic Analysis of Phytase from Aspergillus niger Isolates of an Indonesia Origin - Baraka Stewart Mkumbe; Sajidan Sajidan; Artini Pangastuti; Ari Susilowati; Ralf Greiner (HAYATI Journal of Biosciences, 2022)
This research aimed at analyzing the phytase from fungal isolates SB1, SB2, BS, and WF produced in cornstarch with glucose medium (CS+Glu) as carbon sources and Potatoes dextrose broth (PDB). The activity of phytase from isolates SB1, SB2, BS, and WF produced in CS+Glu medium was 2.97 UmL-1, 2.87 UmL-1, 3.18 UmL-1, and 4.37 UmL-1, respectively, while the activity of phytases was 2.07 UmL-1, 2.17 UmL-1, 2.22 UmL-1, and 2.78 UmL-1 respectively in PDB medium. The optimal temperature of SB1 and WF phytase was 40°C, while SB2 and BS were 50°C and 60°C, respectively. The optimal pH of SB1 and WF phytase was 5.0, while SB2 and BS phytase were 6.0, and 4.0 respectively. 18S rRNA gene analysis revealed that SB1 was 99% identical to Aspergillus niger ANTS (KY825168.1), SB2, BS, and WF were 99% identical to A. niger Moriga leaf (MG889596.1). Multiple sequences and phylogenetic analysis of phytase gene showed that phyA_SB1 and phyA_SB2 were 98% homology with A. ficuum (AAB26466), 97% with A. niger (ADP05107) while phyA_WF was 99% with A. ochraceoroseus (PLB29348), 98% with A. niger (ADP05105). The deduced proteins contain conserved motifs RHGARYPTD at N-terminal while lacking HD motif at C-terminal. These phytases were in the same cluster with Aspergillus sp. phytase A indicating that they belong to Histidine Acid Phosphatases (HAP) family.